2012
DOI: 10.1520/jte104034
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimum Fiber Content in a Fiber-Reinforced Clay

Abstract: The inclusion of randomly distributed short virgin polypropylene fibers (C3H6) in clay has proven to significantly improve the geotechnical properties of clay such as shear, compressive, and tensile strengths, ductility, volume change, and so on. Those improvements have triggered great attention on the possibility of mixing fibers with clay to form a desirable composite. Because the percentage of fibers used is arbitrarily chosen by the users, the purpose of this study is to determine if there is an optimum fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In all cases the individual fibres clumped and matted to form fibrous balls that had to subsequently be prised apart and redispersed in the soil mass. To ensure distribution and prevent fibre balling, air-dried soil powders have been used, into which fibres are incrementally hand mixed prior to the addition of water (Amir-Faryar and Aggour, 2012;Tang et al, 2007). This method ensured the homogeneity of the mix and random orientation, but is not a viable methodology for use on-site.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases the individual fibres clumped and matted to form fibrous balls that had to subsequently be prised apart and redispersed in the soil mass. To ensure distribution and prevent fibre balling, air-dried soil powders have been used, into which fibres are incrementally hand mixed prior to the addition of water (Amir-Faryar and Aggour, 2012;Tang et al, 2007). This method ensured the homogeneity of the mix and random orientation, but is not a viable methodology for use on-site.…”
Section: 2mentioning
confidence: 99%
“…A search of the literature showed that testing has typically been done utilising fibre contents of 0·05-1·25%, with a small number of tests having been conducted using higher contents of around 3-5%, although with difficulty (Al-Wahab and Al-Qurna, 1995;Al-Wahab and Heckel, 1995;Amir-Faryar and Aggour, 2012;Anagnostopoulos et al, 2014;Cai et al, 2006;Chegenizadeh and Nikraz, 2011;Estabragh et al, 2012;Fowmes et al, 2006;Freitag, 1986;Zaimoglu and Yetimoglu, 2011). In the initial compaction tests done in this study, fibre contents of 0·25% and 0·75% were used in order to obtain values at the lower and higher ends of the range.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Nowadays, the design and construction of many civil engineering projects require incorporating weak soils with very low bearing capacity and shear resistance ( Mirzababaei et al., 2018 ). Therefore, it is extremely necessary to use various ground improvement techniques of which reinforcing soil deposits with discrete randomly distributed fibers is an attractive method that has recently become a focus of interest ( Tang et al., 2007 ; Amir-Faryar and Aggour, 2012 ; Hejazi et al., 2012 ; Mirzababaei et al., 2013 ; Baruah, 2015 ; Bozyigit et al., 2017 ; Qadir, 2017 ; Qadir et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adding natural fibers to reinforce construction materials originated in ancient times ( Akbulut et al., 2007 ; Al-Adili et al., 2012 ; Hejazi et al., 2012 ; Zaimoglu and Yetimoglu, 2012 ; Noorzad and Amini, 2014 ; Salim et al., 2018 ) when civilizations in Mesopotamia added straw to prepare reinforced sun-dried soil bricks. The main purpose of this mixture was to enhance the soil integrity by improving its properties and reducing the growth of potential cracks ( Freitag, 1986 ; Amir-Faryar and Aggour, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of recent research shows that the geotechnical properties of fiber reinforced composites are dependent on the percentage of fiber inclusion, which indicates that geotechnical properties of the fiber-clay composite can vary with respect to different fiber contents (Amir-Faryar & Aggour, 2012a).…”
Section: Introductionmentioning
confidence: 99%